Anthropogenically-forced weakening of the Indian summer monsoon and enhancement of the western North Pacific tropical cyclogenesis - Sagar, Aswin; Krishnan, R.; Sabin, T. P. (Frontiers in Earth Science, 2023)
: This study addresses the role of human-induced climate change on the interactions of convective activities between the Indian summer monsoon (ISM) and western North Pacific (WNP) regions - an important scientific issue which has been hitherto overlooked. We have examined this problem using two numerical experiments of a high-resolution climate model, with and without anthropogenic forcing (i.e., HIST and HISTNAT) for the historical period 1951-2005, supplemented by innovative diagnostics like causal network analysis. Our findings suggest that an anthropogenically-forced weakening of the ISM circulation tends to significantly enhance the genesis potential index (GPI) of the WNP tropical cyclones by 13.5% and associated convective activities, by reorienting the large-scale flow over the tropical Indo-Pacific in a manner that is conducive for enhancement of the WNP tropical cyclogenesis. Additionally, it is found that the probability of extremely low sea-level pressure (SLP) (< 995.5 hPa) around Taiwan and Chinese mainland is significantly higher by 10.3% in the anthropogenically-forced simulation as compared to the natural run. Using the model outputs from HIST and HISTNAT, we also performed a causal effect network (CEN) analysis to understand the causal connections among the three indices involved in the ISM-WNP interactions (a) Indian monsoon circulation index (IMI) which is the difference in the area-averaged 850 hPa zonal winds between the boxes (40oE-80oE, 5oN-15oN) and (70oE-90oE, 20oN-30oN) (b) WNP tropical cyclone activity expressed as the genesis potential index (GPI) averaged over the region (120oE-180oE, 5oN-30oN) and (c) Tropical Indo-Pacific wind index (IPWND) which is based on the 850 hPa zonal winds averaged over the domain (100oE-130oE, 5oN-20oN). Results from the CEN analysis indicate that an anthropogenically-forced weakening of the IMI can lead to possible strengthening of GPI and IPWND with time-lags of 5 days and 7 days, respectively. In general, it is noted that the causal relationships among IMI, GPI and IPWND are associated with shorter time-lags (~ 4–9 days) in HIST and longer time-lags (~ 19-28 days) in HISTNAT.